Customer relationship management implementation in Iran automobile industry - Kavosh, Kamyar (2011)
Customer relationship management (CRM) has become popular among organizations and firms, hence many have implemented it in order to compete with others and promote their businesses. In CRM implementation, there are barriers, critical success factors and the strategic components that should be determined. A CRM model was used to determine the CRM barriers, critical success factors and show the current implementation of CRM in the Iran automobile industry. The proposed CRM model can be used by different organizations to identify the critical success factors, barriers and the position of their CRM project. To do this, nine automobile manufacturers were investigated. The automobile industry is chosen because it is a strategic and crucial industry to Iran. Besides that, the investigated companies also plan to penetrate in the international market. According to previous investigations and databases, currently, this study is the first done in the Iran automobile industry. Data were gathered through several in-depth interviews and observations conducted among the managers and non-managers. Two stages of analysis were performed, they were case analysis and cross case analysis. The findings show that the studied companies have experienced some difficulties in implementing CRM. An example of the difficulties identified is cultural barrier. Besides that, the critical success factors have been recognized. This research also reveals that the most important components of CRM implementation are people, process, and technology. Another contribution of this study is identifying new items in Iranian settings such as the in-house or outside trainers. This study shows that in-house trainers are more efficient and effective in training employees for CRM projects. In addition to that, the level of CRM knowledge of trainers is vital in getting the expected results.